Numerical Simulation on the Basic Rules of Multihole Linear Codirectional Hydraulic Fracturing - Weiyong Lu; Yonglong Wang; Xin Zhang (Geofluids)
Directional rupture is one of the most important and common problems in rock breaking engineering. The purpose of directional rock breaking can be effectively realized by using multihole linear codirectional hydraulic fracturing. In this paper, realistic failure process analysis (RFPA) software is used to verify the experimental results of multihole linear codirectional hydraulic fracturing and investigate its basic law. The following results are demonstrated: (1) RFPA software can be very helpful to study the basic law of multihole linear codirectional hydraulic fracturing; (2) the process of multihole linear codirectional hydraulic fracturing can be divided into four stages: water injection boost, fracture initiation, stable fracture propagation, and fracture connection; and (3) multihole linear codirectional hydraulic fractures propagate along the direction of borehole distribution. Multihole codirectional hydraulic fracturing is influenced by the angle between the direction of the hole distribution and maximum principal stress, the difference of the principal stress, and the spacing of the boreholes. The smaller the angle, the difference value of the principal stress, and the hole spacing, the better the multihole codirectional hydraulic fracturing effect.